2015
DOI: 10.1260/2040-2295.6.2.159
|View full text |Cite
|
Sign up to set email alerts
|

Epileptic Seizure Detection and Prediction Based on Continuous Cerebral Blood Flow Monitoring – a Review

Abstract: Epilepsy is the third most common neurological illness, affecting 1% of the world's population. Despite advances in medicine, about 25 to 30% of the patients do not respond to or cannot tolerate the severe side effects of medical treatment, and surgery is not an option for the majority of patients with epilepsy. The objective of this article is to review the current state of research on seizure detection based on cerebral blood flow (CBF) data acquired by thermal diffusion flowmetry (TDF), and CBF-based seizur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…An increase in Na + influx leads to depolarization, causing vascular neuronal damage to a certain extent. In particular, when the endothelial function of the local capillaries is damaged, local CBF is reduced ( Barth and Mody, 2011 ; Gooshe et al, 2015 ; Tewolde et al, 2015 ). Therefore, we can speculate that the IFGtriang is vascularly dysfunctional, and that decreases in CBF lead to the destruction of the vascular barrier, glial hyperplasia, and inflammation and induce excessive excitement of neuronal networks, thereby promoting epilepsy and leading to reduced perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in Na + influx leads to depolarization, causing vascular neuronal damage to a certain extent. In particular, when the endothelial function of the local capillaries is damaged, local CBF is reduced ( Barth and Mody, 2011 ; Gooshe et al, 2015 ; Tewolde et al, 2015 ). Therefore, we can speculate that the IFGtriang is vascularly dysfunctional, and that decreases in CBF lead to the destruction of the vascular barrier, glial hyperplasia, and inflammation and induce excessive excitement of neuronal networks, thereby promoting epilepsy and leading to reduced perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…In epileptic model and patients, abnormal capillary vasodynamics are mediated by mural cell constrictions which is complex and changeable (Leal-Campanario et al, 2017). While blood flow contribute to epilepsy is controversial (Tewolde et al, 2015), we found that FDG uptake in the epileptic foci was minimally affected by influx and efflux of FDG.…”
Section: Discussionmentioning
confidence: 71%
“…The implanted thermal diffusion flowmeter sensor, the SABER 2000 (SABER 2000; Flowtornics, Phoenix, AZ, USA), 4 34) was used to measure the brain cortex surface temperature in 52 cases, between 1997 and 2002. The Bowman perfusion monitor (Hemedex, Waltham, MA, USA,) 21 29) was used to measure the brain cortex temperature at about 1–2 cm below the surface in 83 cases, between 2003 and 2009.…”
Section: Methodsmentioning
confidence: 99%